Key Factors Influencing Credit Risk of Islamic Bank: A Malaysian Case - Ahmad, N. H.; Ahmad, S. N. (Universiti Sains Islam Malaysia, 2024)
The rapid and dynamic changes in the global financial landscape pose various risks to banking institutions. Operating side by side with conventional banks, Islamic banks are equally vulnerable to risks. The future of Islamic financial institutions will depend to a large extent on how well they manage risks. This ability could be enhanced if the factors affecting these risks are systematically identified. This paper examines the factors affecting credit risk, being the main risk faced by banking institutions and systematically identifies the key factors influencing credit risk formation in Islamic banking operations in Malaysia. A comparison of these factors between Islamic and conventional banking operations is highlighted. Several policy implications are addressed to promote risk management culture in Islamic banking industry.